Synergism in the Solvation of Solvatochromic Probes in Binary Mixtures with Ionic Liquids - Caroli-Rezende, M (Elsevier B.V., 2023)
The preferential solvation of two perichromic dyes, 4-amino-N-methylphthalimide (4-AMP) and Nile Red (NR) in binary mixtures of an ionic liquid ([bmim][X], where X = BF4, PF6, Tf2N and DCA) with a protic or non-protic solvent, was investigated, in search of examples of a synergetic or “hyperpolar” behavior. Synergism was generally observed in those mixtures where the two pure components had similar polarity values, according to the employed probe. A parallel was drawn between the observed synergism in these IL mixtures and the phenomenon of hydrotropism, also observed with organic solutes in aqueous IL mixtures. More generally, in binary mixtures with organic solvents, ionic liquids can act as solvatotropes, promoting the dye solvation by formation of solute-specific aggregates with all species present in the mixture. By stabilizing the dipolar excited state of 4-AMP or NR through hydrogen-bonds and electrostatic interactions in these aggregates, a “hyperpolar” milieu is generated, which surpasses the polarities of the two pure components. Solvatotropism seems to offer a more realistic picture than the solvent-exchange model, originally developed for simpler systems, to the phenomenon of preferential solvation in binary mixtures with ionic liquids. © 2023 Elsevier B.V.